Pengaruh Metode Preview, Question, Read, Summarize and Test (PQRST) Terhadap Peningkatan Keterampilan Membaca Pemahaman Siswa Kelas V A SDN Paccinongang Unggulan - Rahmania Rusman; Ummu Khaltsum; Muhammad Saeful (STIKes Ibnu Sina Ajibarang, 2024)
This research is a type of experimental research with the One Group Pretest- Posttest research design to see whether there is an effect of the PQRST method on improving reading comprehension skills of V A SDN Paccinongan Unggulan. So this study aims to find out: (1) an overview of the application of the PQRST method to improving reading comprehension skills of class V A SDN Paccinongan Unggulan (2) how to improve students' reading comprehension skills class V A SDN Paccinongan Unggulan after using the PQRST method (3) is there any effect of the PQRST method on improving reading comprehension skills of class students V A SDN Paccinongan Unggulan. The population in this study were all students of class V A SDN Paccinongan Unggulan, totaling 19 students. This sample uses a saturated sampling technique with a sampling technique when all members of the population are used as samples. Data collection techniques used in this study are observation, testing and documentation. Research data analysis techniques using descriptive and inferential analysis. The conclusions of this study indicate that: (1) The application of the PQRST method (Preview, Question, Read, Summarize and Test) in the learning process goes very well, (2) Students' reading comprehension skills show an increase after using the PQRST method, (3) There is an effect of applying the PQRST method to improving reading comprehension skills of class V A SDN Paccinongan Unggulan Elementary School Makassar City.